EFFECTS OF GROUP GUIDANCE AND COUNSELLING TECHNIQUES ON STUDENTS’ VOCATIONAL MATURITY IN EKITI STATE SECONDARY SCHOOLS, EKITI STATE, NIGERIA - Babatunde, Joseph Ojo; Osakinle, Eunice Olufunmilayo (European Scientific Journal, ESJ, 2013)
The study investigated the effects of group guidance and counselling techniques on students’ vocational maturity. The purpose of the study was to determine whether the Group Career Guidance (GCG) and Group Career Counselling (GCC) techniques will enhance the vocational maturity of secondary school students. To achieve this objective, quasi experimental of pre-test, post-test design was employed. 120 students were selected from senior secondary school class two (SSS 2) through purposive sampling method. The selected students were grouped into two. The groups were exposed to GCG and GCC respectively in their various locations. The groups were tested twice, that is, before and after treatment. The finding revealed that the two techniques are effective in the improvement of students’ vocational maturity.